Estimation of analytical model for enhancement and implementation of an electro-optic switch - Hbeeb, Sadeq Adnan (Iraqi Journal for Electrical and Electronic Engineering, 2018)
This research presents a technique of an electro optic effect for enhancement the an accomplishment of an electro optics switch using Mat lab simulation program . this technique includes design a mathematical model for evaluate the effect of different parameters such as refractive index (n), distance of separation between waveguides (d), length of electrodes (L), relative refractive index (Δn), and switching voltage (V  ), on the DC bias voltage of an electro optics switch. In this work the investigation of performance of an electro optics switch by analysis of an effect of distance between waveguides and the changing of refractive index on the bias voltage (V), and which optimizes when the wavelength is from 1300 into 1550 nm. Finally, an electro-optic active switch is designed and optimized, using the analytical model and which considers important device in the modern optical communication system.